Uso de la inmunohistoquímica como herramienta epidemiológica para el diagnóstico de rabia bovina a partir de casos no conclusivos - Gloria Jurado, G.; Montoya-Flórez, Luis [UNESP]; Cesar Betancur, H.; Pedraza-Ordoñez, Francisco [UNESP] (My University, 2012)
Objective. Identify the rabies virus in cases of nervous disease archived in the laboratory with diagnosis of nonspecific encephalitis. Materials and methods. Twelve samples of bovine brain suspected of rabies, were processed by indirect immunoperoxidase technique using polyclonal antibodies against the viral agent. Results. Was demonstrated the presence of viral antigens in three cases in the form of small aggregates in the cytoplasm of neurons, with a pattern of round or oval and a variable number of viral inclusion bodies. We discussed the importance of the results in Colombia, the usefulness of the technique in the difficult conditions for sending samples to the laboratory, plus the possible relationship of the negative cases with bovine herpesvirus 5. Conclusions. The use of immunohistochemical technique to demonstrate rabies virus antigens in formalin fixed bovines tissues can help in the construction of an epidemiological map of rabies disease in Colombia and may reduce the high under-diagnosis of diseases of the nervous system of cattle, reported in some regions.
Use of immunohistochemistry as an epidemiological tool for the diagnosis of bovine rabies using inconclusive cases
Keywords: Encephalitis; Infections; Rabies virus (Source: CAB)